Assessing the Influence of Trade Unions on Income Redistribution:A Comparative Analysis with Evidence from Armenia - Torosyan, Alik («Տնտեսագետ» հրատ․)
This paper seeks to analyze the contribution of trade unions in tackling the issue of income inequality with special reference to trade union density and its connection with income redistribution. In the paper, we analyze the effects of trade unions on income distribution, employment, and average wages, based on the data collected from 28 countries, including Armenia, during 2009-2019. The results highlight that enhanced trade union density harms income disparity as indicated by the Gini coefficient, and has a favorable impact on average wages. But the impact on employment is still small, comparatively speaking. International comparisons show that unions can mostly minimize income inequality in countries with a high density of trade unions. On the other hand, in nations with a low union density, the equality-reducing capability of unions decreases, and in some situations, the unions directly widen the gap. The study also illustrates that the trade union density has been greatly reduced in Armenia to half over the period under consideration. This decline poses a great threat to the ability of unions to tackle situations where the incomes of the citizens in the country are dwindling. The paper’s implications for the promotion of strong labor market institutions (LMIs) and the reduction of income inequality serve as a valuable guide for policymakers seeking to support and enhance the effectiveness of trade unions while pursuing efforts at enhancing labor market justice.
Keywords: Social policy